Decision and coordination of E-commerce closed-loop supply chains with fairness concern. (May 2023) - Wang, Yuyan; Wang, Dexia; Cheng, T.C.E.; Zhou, Rui; Gao, Junhong
Highlights: we price differentially by considering consumers' preference for remanufactured and new products. we develop the models with or without fairness concern to explore its impact on decision-making. We incorporate a relative fairness reference point into the manufacturer's utility function and find the manufacturer's fairness concern behaviour to punish the e-platform is detrimental to cultivating a remanufactured product consumer market. A new contract of "dual-revenue and service-cost sharing" can effectively eliminate the efficiency loss of the two decentralized models. Abstract: The e-commerce market expands rapidly, and manufacturers sell remanufactured and new products online, making e-commerce closed-loop supply chains face product differential pricing and follower firms' unfair psychology due to the large profit gap between system members. Therefore, we price differentially by considering consumers' preference for remanufactured and new products and develop a centralized model and two decentralized models with or without fairness concern to explore its impact on decision-making. We show that consumers' higher preference for the remanufactured product is conducive to the two products' price and the remanufactured product's sales, then the sensitivity analysis shows that the higher preference positively affects system operation. We next incorporate a relative fairness reference point into the manufacturer's utility function and find the manufacturer's fairness concern behaviour to punish the e-platform is detrimental to cultivating a remanufactured product consumer market and causes the loss of its profits to be greater than that of the e-platform's profit. Additionally, a new contract of "dual-revenue and service-cost sharing" can effectively eliminate the efficiency loss of the two decentralized models. Our paper provides theoretical contributions to product pricing, the setting of a utility function with fairness concern, and the design of dual coordination mechanism.